A Prototype Design of Water Filtration System and Recycling System for Flushing Toilet - Nurdalila Saji; Nur Aslini Roslan (Progress in Engineering Application and Technology, 2020)
Water is an invaluable source of nature, each resident needs water for their daily needs. Plus, water is a very important source in generating various economic income in areas such as agricultural, industrial, fisheries, and generation of electricity sources. However, people nowadays are being irresponsible with the use of water. The World Health Organization (WHO) has reported that every individual worldwide using water resources between 50 to 165 liters per day. In Malaysia, the population of wasting water exceeding international standards. Therefore, to minimize the water wastage, an initiative is taken to overcome the problem with the prototype design of a water filtration system and a recycling system for a flushing toilet to filter wastewater or greywater from the kitchen sink, toilet sink and floor trap in bathrooms. The purpose of this study is to design a prototype, produce, and test the effectiveness of the prototype design so that the water filtration system is veritable. This prototype uses natural ingredients and economical products to clean wastewater and it uses the gravity system. This prototype uses natural ingredients and economical products to clean wastewater and it uses the gravity system. Tests involved in the examination of the prototype of the water filtration system are leak detection test and refined water cleanliness quality test. The water hygiene quality test is to obtain the value of pH, TSS, TDS, and BOD. Besides, water hygiene test is done to ensure that the filtered water is not greasy, eliminate soap foam and solid waste such as hair. The prototype is set up and placed on a house sink to reduce water pollution. This project focuses on the filtered water from the kitchen sink, toilet, and floor trap for the flushing toilet system. The flushing toilet system usually uses direct water. Thus, by using this prototype, it can minimize water wastage and reduce the water tariff rate.